Science Self-Efficacy (SSE) Relationship on Cognitive Learning Outcomes amongst The Ecology Concept - Marsha Hemalia Putri; Nailil Inayah; Maunah Setyawati; Rizka Novia Rochmawati (Integrated Science Education Journal, 2026)
Purpose of the study: Science Self-Efficacy (SSE) is important for students because it is directly related to their belief in their ability to learn and complete science tasks. Students with high SSE tend to be more confident, do not give up easily when faced with difficulties, and have greater motivation and involvement in the science learning process. This study aims to determine the effect of SSE on students’ cognitive learning outcomes in the Ecology concept, focusing solely on identifying the relationship between these two variables. Methodology: This research utilized a quantitative ex post facto correlational design with Simple Random Sampling. The instruments used were a 30-item Science Self-Efficacy (SSE) questionnaire and a cognitive learning test. Data were analyzed using descriptive statistics and Spearman’s rank correlation in SPSS version 27 to determine relationships among variables. Main Findings: The study revealed that students’ Science Self-Efficacy (SSE) was predominantly categorized as High, with 60% of participants reaching this level. The Spearman correlation coefficient of 0.623 and the significance value of 0.001 indicated a positive, significant relationship between SSE and cognitive learning outcomes. These findings confirm that higher levels of SSE strongly contribute to improved cognitive performance in learning the Ecology concept. Novelty/Originality of this study: This studies rarely examine Science Self-Efficacy (SSE) as a domain-specific construct related to higher-order cognitive outcomes in Ecology, its dimensions (magnitude, strength, and generality), or evidence from multicultural contexts such as Indonesian schools abroad.